Implementasi Program Ta’lim dalam Membina Akhlak Siswa di MTs Swasta Sabila Hamparan Perak - Lutfi Rizal Putra; Zulfiana Herni (EduInovasi: Journal of Basic Educational Studies, 2024)
Morals are one of the factors that greatly determine the rise and fall of a person, nation or country. In building and fostering the morals of the nation's generation, they have an important role. This study discusses a program called the ta'lim program implemented by one of the schools in Deli Serdang in fostering morals by using the book "Fadhilah Amal" as a guidebook in the program. This study aims to determine the ta'lim program and teaching methods used in the program. This study uses a qualitative descriptive design to analyze the implementation of the ta'lim program. This study uses the theory of Ibnu Miskawaih and Abdullah Nashih Ulwan in implementing methods of educating children, this theory is used because it is relevant to the research and the ta'lim program implemented in schools. The data for this study were collected using observation, recordings, interviews, questionnaires and also six meetings during the ta'lim program process running directly. Data collection used through observation, interviews and documentation. Checking the validity of the data used is triangulation of sources and methods. This study used discourse analysis to describe the data that the author found during observations and interactions in class. The data can be identified and analyzed descriptively. The results of the study show (1) the profile of the school where the research was conducted, (2) the educational staff at MTs Sabila Hamparan Perak, (3) the implementation of the ta'lim program and the development of students' morals and (4) the implementation of the ta'lim program and the development of students' morals.